Filter cake in industrial quality and in the physiological and acid phosphatase activities in cane-plant - Vasconcelos, Ricardo de Lima [UNESP]; Almeida, Hilário Júnior de [UNESP]; Prado, Renato de Mello [UNESP]; Santos, Luiz Flávio José dos [UNESP]; Pizauro Júnior, João Martins [UNESP] (Elsevier, 2017)
Sugarcane filter cake, a phosphorus-rich (P) fertilizer, can affect not only P storage in sugarcane (Saccharum officinarum L.), but also its metabolism and photosynthesis. In this study, was evaluated the effect of different mineral fertilizers, with and without the use of filter cake, on P levels, gas exchange, acid phosphatase activity, sugar, hydrated alcohol production, and total soluble solids. Sugarcane (variety RB86 7515) was cultivated on dystrophic Typic Haplustox in a randomized complete block design. Three replicates were established in a 3 × 4 × 2 factorial scheme, with three P sources (Triple Superphosphate-TS, Natural Reactive Bayovar Phosphate-BP, and Natural Araxa Phosphate-AP), four rates of P as P2O5 (0, 90, 180, and 360 kg ha−1), and the presence or absence of filter cake (7.5 Mg ha−1, dry weight). The levels of foliar P (PCL) were determined, along with the accumulation of P in aerial plant parts (AAP), net CO2 assimilation (A), stomatal conductance (gs), transpiration rate (E), acid phosphatase activity (APL), hydrated alcohol, total soluble solids (TSS), total recoverable sugar (TRS), and stalk production. The highest P rate with filter cake yielded the maximum concentration of P in leaves (1.7 g kg−1), leading to the highest P accumulation in aerial plant parts (17.8 kg ha−1), and furthering a sugar production of 197.1 kg t−1, and stalk production (122.6 Mg ha−1). The highest rate of Triple Superphosphate alone or with filter cake yielded the lowest acid phosphatase activity, the highest rate increased the accumulation of P in aerial parts (18.8 kg ha−1), and for stalk production, produced 123.1 Mg ha−1 of stalks. The use of Triple Superphosphate associated with filter cake increased the production of sugar (192.5 kg t−1), hydrated alcohol (91.3 L t−1) and total soluble solids (18.4°Brix), while the use of higher P rates, regardless of the source, increased gaseous exchange in sugarcane plants.
Keywords: Hydrated alcohol; Photosynthesis; Stomatal conductance; Total soluble solids; Triple superphosphate